A scoping review of augmented reality in nursing - Hanna Wüller; Jonathan Behrens; Marcus Garthaus; Sara Marquard; Hartmut Remmers (BMC, 2019)
Abstract Background Augmented reality (AR) has the potential to be utilized in various fields. Nursing fulfils the requirements of smart glass use cases, and technology may be one method of supporting nurses that face challenges such as demographic change. The development of AR to assist in nursing is now feasible. Attempts to develop applications have been made, but there has not been an overview regarding the existing research. Objective The aim of this scoping review is to provide an overview of the current research regarding AR in nursing to identify possible research gaps. This led to the following research question: "To date, what research has been performed regarding the use of AR in nursing?". A focus has been placed on the topics involving cases, evaluations, and devices used. Methods A scoping review was carried out with the methodological steps outlined by Arksey and O'Malley (2005) and further enhanced by Levac et al. (2010). A broad range of keywords were used systematically in eight databases including PubMed, Web of Science and ACM to search for topics in nursing. Results The search led to 23 publications that were included in the final analysis. The majority of the identified publications describe pilot studies. The methods used for identifying use cases and evaluating applications differ among the included studies. Furthermore, the devices used vary from study to study and may include smart glasses, tablets, and smart watches, among others. Previous studies predominantly evaluated the use of smart glasses. In addition, evaluations did not take framing conditions into account. Reviewed publications that evaluated the use of AR in nursing also identified technical challenges associated with AR. Conclusions These results show that the use of AR in nursing may have positive implications. While current studies focus on evaluating prototypes, future studies should focus on performing long-term evaluations to take framing conditions and the long-term consequences of AR into consideration. Our findings are important and informative for nurses and technicians who are involved in the development of new technologies. They can use our findings to reflect on their own design of case identification, requirements for elicitation and evaluation.